MORAL TELEOLOGY IN ETHICAL CRITIQUE OF THE ECONOMISM - H. Ilina (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper considers the moral teleology in terms of ethical critique of the economism. Responsibility as an ethical category is interpreted in terms of economic ethics and taking into account the genetic relationship between the economy and morality. The alternative interpretation of ideas of the economism in business ethics is identified. The influence of ethical responsibility to the formation of new styles of economic and management thinking is revealed.